CHLORIDE EFFECTIVE DIFFUSION COEFFICIENT OF CONCRETE - Shafikhani, Mehdi (My University, 2019)
For concrete, a sustainable design requires considering both mechanical properties and durability. One of the major deterioration modes of reinforced concrete structures is the entry of chloride ions and corrosion of embedded metals, which is mainly controlled by diffusion as the mass transport mechanism. Therefore, it is pivotal to quantify the chloride diffusion coefficient of concrete, which controls the rate of chloride ingress. Several testing methods exist for quantifying diffusivity of concrete. However, the current test methods are time consuming and demanding. The primary goal of this study is to develop models for quantifying the chloride diffusion coefficient of concrete. As such, initially, the most recent and prevailing analytical models proposed in the scientific literature were critically reviewed and the parameters controlling the chloride diffusion coefficient of concrete were identified. Then, the cement degree of hydration of concrete – as a key parameter which controls the properties of concrete – its measurement methods, and the uncertainties associated with different quantification methods were scrutinized. Finally, three models were developed to quantify the chloride diffusivity of concrete. The first model quantifies the chloride diffusivity of concrete in terms of its electrical resistivity based on the modified Nernst-Einstein equation. The model accounts for the ionic concentration of the pore solution through the alkalis released due to hydration of cementing materials and the alkali uptake of hydration products, the pore solution conductivity, and the interaction between the ions in the pore solution. The second model, which provides a phenomenological relationship for chloride diffusivity of concrete in terms of its compressive strength, accounts for the tortuosity factor of the mixture, aggregate volume fraction, porosity, compressive strength, and cementing materials content and composition. The third model is developed based on the mixture constituents and the cement degree of hydration of concrete. The model accounts for tortuosity factor through the volume fraction of aggregate particles, the interfacial transition zone thickness and diffusivity, cementing materials type and chemical composition, bulk cement paste transport properties through water to cementing materials ratio, cement degree of hydration, supplementary cementing materials type and replacement levels. In order to assess the accuracy and precision of the proposed models, an experimental program was developed and conducted. The following variables were considered for the experimental program: the volume fraction of coarse aggregate, water to cementing materials ratio, total cementing materials content, and supplementary cementing materials type and replacement levels. The experimental results along with the reported data in the scientific literature were used to validate the proposed models. The results revealed the capability of the models to capture the documented observations, as well as the high accuracy and precision of the proposed models for quantifying the chloride diffusivity of concrete in a wide range of concrete mixtures composition and age. The developed models provide designers, practicing engineers and standard/code developers with accurate, precise and consistent models for quantifying the chloride diffusion coefficient of concrete as a direct measure of its durability.
Keywords: Concrete; Chloride; Durability; Diffusion Coefficient; Model